Ligature Versus Transvenous Endovenorrhaphy for Closure of Side-to-Side Arteriovenous Fistula Created for Hemodialysis - Khoshnevis, Jalaladin; Sobhiyeh, Mohammad Reza; Tadayon, Niki; Molaee Govarchin Ghalae, Hojat; Kalantar Motamedi, Mohammad Reza (Urology Journal, 2011)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Purpose: To report a novel technique for arteriovenous fistula (AVF) closure in side-to-side fistulas. Materials and Methods: One hundred and sixty-two patients with sideto- side AVFs, who were candidates for AVF closure, were randomly divided into two groups: group A (84 patients) who underwent AVF ligature and group B (78 patients) who underwent AVF closure using transvenous endovenorrhaphy technique. Both procedures were conducted by the same surgical team. The patients were followed up for 6 months. Results: Of 124 patients with proximal AVFs, 65 (52%) subjects underwent ligation and 59 (42%) transvenous endovenorrhaphy. Of 38 patients with distal AVFs, half underwent ligation and for the remainder, transvenous endovenorrhaphy was done. Failure of AVF closure was detected in 28 (17%) patients; 25 (89.28%) were in group A and 3 (10.71%) were in group B. All of these recurrences were successfully treated by transvenous endovenorrhaphy technique. Conclusion: We claim that significant lower failure rate of transvenous endovenorrhaphy makes it the technique of choice, especially for side-to-side AVFs.